2013
DOI: 10.5740/jaoacint.sgealtintas
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Constituents from Origanum onites and Their Antifungal and Antibacterial Activity

Abstract: Essential oils obtained by hydrodistillation (HD) and microwave-assisted HD (MWHD) of Origanum onites aerial parts were analyzed by GC and GCIMS. Thirty-one constituents representing 98.6% of the water-distilled oil and 52 constituents representing 99.6% of the microwave-distilled oil were identified. Carvacrol (76.8% HD and 79.2% MWHD) and thymol (4.7% HD and 4.4% MWHD) were characterized as major constituents in both essential oils. Separation of carvacrol and thymol was achieved by overpressured layer chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 0 publications
0
37
0
3
Order By: Relevance
“…Results of various studies indicated that the antioxidant effects of oregano might be related to the dominant components including carvacrol and pulegone, presentin its essential oil (8). The essential oil of various Origanum species can contain a number of additional chemical constituents (9) including linalool, gamma-terpinene, p-cymene and terpinene-4-ol (9,10). Origanum has long been valued for its culinary, fragrant and medicinal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Results of various studies indicated that the antioxidant effects of oregano might be related to the dominant components including carvacrol and pulegone, presentin its essential oil (8). The essential oil of various Origanum species can contain a number of additional chemical constituents (9) including linalool, gamma-terpinene, p-cymene and terpinene-4-ol (9,10). Origanum has long been valued for its culinary, fragrant and medicinal properties.…”
Section: Introductionmentioning
confidence: 99%
“…2) delayed the increase of total aerobic bacterial count as their numbers significantly increased after 120 h of experiment by 4.56 log CFU/g and 4.39 log CFU/g, respectively ( P ≤ 0.05). This effect was expected as one of the main thyme constituents, carvacrol, was earlier determined to have an antibacterial and antifungal activity (Altintas and others ). Also, the effect of carvacrol was enhanced by the addition of cinnamaldehyde, lactic acid and linalool, which is well known for the antimicrobial activity against various pathogens like tested C. jejuni , Bacillus subtilis , Escherichia coli , Pseudomonas aeruginosa , and Staphylococcus aureus (Ravishankar and others ; Mild and others ; Chan and others ).…”
Section: Resultsmentioning
confidence: 77%
“…The major constituents of oregano oil are carvacrol, thymol, and p-cymene. However the ratios of these constituents can vary widely depending upon extraction method and plant growth conditions [15,16]. GC-MS quantification of the particular oil used in this study showed 77% carvacrol, 10% p-Cymene, and 7% thymol (GC-MS integration values not shown).…”
Section: Discussionmentioning
confidence: 99%